Template-free fabrication of single-crystalline calcite nanorings during crystal growth in water. Issue 1 (8th November 2019) - Kezuka, Yuki; Yoshida, Maya; Tajika, Masahiko
Abstract : Formation of a calcite nanoring with a single cavity was confirmed during its crystal growth in an aqueous system. Abstract : Morphology evolution of calcite nanoparticles was investigated in detail during crystal growth induced by containing their aqueous slurry at a temperature of 95 °C. Formation of a single-crystalline nanoring that has a single cavity was confirmed soon after the slurry temperature was elevated to 95 °C. No templates were employed during the crystal growth process.